Popular Egyptian cinema : gender, class, and nation - Shafik, Viola, 1961- (Cairo, Egypt ; New York : American University in Cairo Press, 2007)
Viola Shafik examines popular and commercial movies from Egypt's film industry, including a number of the biggest box-office hits widely distributed in Egypt and the Arab world. She examines these films against the backdrop of the country's overall socio-political development, from the emergence of the film industry in the 1930s, through the Nasser and Sadat eras, up to the era of globalization.
Part I. Nation. The other ; The allegorical nation -- Part II. Gender. Feminism and femininity ; Female stardom, myth production, and morality -- Part III. Class. Negotiating class through genre ; Audiences and class.
Includes bibliographical references (pages 327-338) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Motion pictures -- Social aspects -- Egypt -- History; Motion pictures -- Egypt -- History; Sex role in motion pictures; Social classes in motion pictures; National characteristics in motion pictures; Cinéma -- Aspect social -- Égypte -- Histoire; Cinéma -- Égypte -- Histoire; Rôle selon le sexe au cinéma.; Classes sociales au cinéma.; Caractéristiques nationales au cinéma.; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- Reference; Motion pictures -- Social aspects; Motion pictures; National characteristics in motion pictures; Sex role in motion pictures; Social classes in motion pictures; Egypt; Film; Ägypten; Massenkultur; Geschichte 1920-2005.; Electronic books; History